Pengaruh Rasio Keuangan Terhadap Financial Distress Pada Perusahaan Manufaktur Yang Terdaftar Di Jakarta Islamic Index 70 (JII70) Periode 2018-2021 - Fajrul Hakim, Muhammad; Hakim Al Faqih, Nur Iman (Universitas Dian Nuswantoro, 2024)
Financial management is very important and vital for a company to maintain its business continuity and avoid financial distress. Financial distress is a condition of financial difficulties that can cause bankruptcy in a company which can be characterized by low financial ratios. This quantitative study aims to determine the effect of financial ratios on financial distress partially and simultaneously on the financial distress conditions of manufacturing companies listed on the Jakarta Islamic Index 70 (JII70) during the 2018-2021 period. This research involved 48 annual financial reports from 12 manufacturing companies in JII70 during the 2018-2021 period obtained from a purposive sampling technique. Data analysis used panel data regression which was processed using Eviews12 software. The results of this study indicate that financial ratios consisting of liquidity, solvency, activity and profitability ratios significant effect on financial distress. Then partially, the liquidity ratio and activity ratio have a positive and significant effect on financial distress. The solvency ratio has a negative and significant effect on financial distress. Meanwhile, the profitability ratio has no effect on financial distress. Following up on the findings of this study, companies need to pay attention to their financial ratios so they can avoid financial distress.